Global Malmquist indices of productivity change in Egyptian wheat production - Elasraag, Yahia H.; Alarcón, Silverio (Spanish Journal of Agricultural Research, 2017)
This study aims to measure the total factor productivity of the main governorates of wheat production in Egypt during the time period 1990-2012 and decompose it into technical change, efficiency change and scale change. We used Global Malmquist TFP index as a non-parametric approach. The results indicated that the contribution of technical change component is more important than the efficiency change component. In fact technical change rose, 25.7%, while efficiency change presented a little decline, 3.7%. The decomposition of efficiency change indicated that the main problem of wheat production in Egypt was scale efficiency that worsened by 5.5%.